Self-cleaning anti-icing high-voltage line insulator and manufacturing method thereof

CN122991774APending Publication Date: 2026-10-27WANGDU JIZHONG ELECTRIC PORCELAIN APPLIANCE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611136996.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

锡锑铁固溶半导体釉虽具备一定的电热融冰能力,但其釉料中功能填料占比高达百分之三十五至四十,原料成本显著偏高,且该体系依赖强氧化气氛烧成,必须使用专用高氧窑炉,常规还原窑炉下生产会导致电阻率大幅漂移,工艺适应性极差;同时全伞施釉后运行泄漏电流最高可达三百微安,在二百二十千伏高压工况下功耗严重超标

Benefits of technology

[0027]①本发明突破了传统全伞单一功能涂层的设计局限,首次基于重冰区瓷绝缘子冰闪失效的区域分异机理,将伞上表面过冷水撞击覆冰区与伞下沿融滴冰棱生长区进行差异化精准设防。伞上表面B区疏水釉凭借≥145°的高水接触角与≤10°的低滚动角,使过冷水滴在冻结前即滚落离开伞面,从源头抑制初始覆冰的形成;伞下沿A区弱半导釉利用碳化硅与鳞片石墨构成的半导体网络,在高压电场下产生可控焦耳热,对伞下沿冰棱生长区实施局部定向融冰,阻断相邻伞裙冰棱的贯通路径。两区功能互补、协同作用,同步实现了“源头减冰”与“中段阻断冰棱”的双重防护目标,从根本上解决了传统疏水釉全伞覆盖时加速冰棱桥接、传统自热釉全伞覆盖时漏流超标的固有矛盾。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991774A_ABST
    Figure CN122991774A_ABST
Patent Text Reader

Abstract

The present application relates to high-voltage transmission and power transmission porcelain insulator technical field, especially to a kind of self-cleaning anti-icing high-voltage line insulator, including porcelain insulating piece, iron cap and steel foot, the porcelain insulating piece is integrally formed with umbrella skirt structure, the porcelain insulating piece surface is divided into A area, B area and C area, three areas share the same base white glaze and three areas thermal expansion coefficient difference <0.3×10 ‑6 / K;The A area is the annular narrow band of umbrella lower edge 0-3cm from umbrella edge, is applied with single layer weak semi-conductive glaze, weak semi-conductive glaze includes silicon carbide micro powder and flaky graphite, after firing, the volume resistivity of A area is 10 8 ~10 9 Ω·cm;The B area is all umbrella upper surface, is applied with fluorine modified nano-hydrophobic glaze, glaze surface water contact angle ≥145°, rolling angle ≤10°;The C area is the porcelain insulating piece surface except A area and B area, is applied with base white glaze;The A area and B area form glaze layer gradual change overlapping zone at umbrella edge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-voltage power transmission and transformation porcelain insulators, and more specifically, to a self-cleaning, anti-icing high-voltage line insulator and its manufacturing method. Background Technology

[0002] In the operation of transmission lines in heavy icing areas, ice flashover faults in porcelain insulators are one of the main factors threatening the safe and stable operation of the power grid. Long-term observation and failure analysis have shown that the core mechanism of ice flashover in porcelain insulators in heavy icing areas is not simply overall icing, but exhibits significant regional differentiation characteristics. Specifically, after supercooled water droplets from freezing rain impact the upper surface of the insulator umbrella, they adhere to that area and gradually freeze to form the initial icing layer. Simultaneously, melted ice from the upper umbrella surface drips under gravity to the lower edge of the lower umbrella, where it continues to freeze and grows downwards along the lower edge as ice ridges. When the ice ridges between adjacent umbrella skirts extend and eventually connect, the effective creepage distance of the insulator string is significantly shortened, ultimately triggering a power frequency ice flashover accident. This failure process reveals that impact icing on the upper surface of the umbrella and the growth of melted ice ridges along the lower edge are two distinct icing behaviors with vastly different physical mechanisms and clearly defined spatial regions. Their combined effect leads to a rapid deterioration of the external insulation performance of the insulator.

[0003] To address the aforementioned ice flashover problem, the industry has explored various anti-icing technologies, but all have insurmountable drawbacks. Regarding pure structural improvements, existing large-diameter anti-icing insulators typically employ a 500-700 mm diameter disc with a radially uniform under-umbrella support ridge structure. This design only physically blocks large-scale icicles that have already formed, but cannot suppress the initial icing process of supercooled water on the umbrella surface. Furthermore, the ice flashover voltage increase achieved solely through structural optimization is only about 9%, offering limited improvement and failing to meet the stringent operational requirements of heavy icing areas. As for hydrophobic glaze solutions for the umbrella surface, potassium feldspar-based composite nanofillers and fluorine-modified systems are currently widely used, attempting to reduce icing by utilizing low surface energy to cause water droplets to roll off. However, actual operation shows that the lower edge of the umbrella is precisely the core area for ice crystal growth. The hydrophobic surface actually accelerates the formation of water droplets and promotes their rapid downward extension, objectively exacerbating the bridging risk of ice crystals. The measured improvement in ice flash voltage is only 3% to 5%, a negligible improvement. Some solutions add high-cost raw materials such as porous graphene to improve performance, further resulting in poor economics for mass production and difficulty in engineering promotion. In terms of the full-umbrella self-heating semiconductor glaze solution, multiple technical branches have encountered bottlenecks. Although tin-antimony-iron solid solution semiconductor glaze has a certain electrothermal ice melting capability, the functional filler content in its glaze is as high as 35% to 40%, resulting in significantly high raw material costs. Moreover, this system relies on strong oxidizing atmosphere firing and must use a special high-oxygen kiln. Production in conventional reduction kilns will cause a large drift in resistivity, resulting in extremely poor process adaptability. At the same time, the leakage current after full-umbrella glazing can reach up to 300 microamps, and the power consumption is seriously exceeded under 220 kV high voltage conditions. Barium titanate-based positive temperature coefficient self-heating glazes rely on lanthanide rare earth elements to regulate the Curie temperature to match environmental conditions. The glaze cost is more than three times that of ordinary glazes, and leakage is uncontrollable after full umbrella coverage. Self-heating power consumption is excessive at low temperatures, and long-term operation accelerates glaze aging, shortening the insulator's lifespan. Furthermore, while traditional silicon carbide conductive glazes have a known process in the industry, they require a three-layer composite glaze application—a base material, a conductive layer, and a protective layer—resulting in a total glaze thickness of 500 to 2000 micrometers and undergoing three firings. This process is extremely complex and inefficient, and this technology has never been applied to the specific scenario of directional de-icing along a narrow band under the insulator umbrella.

[0004] In summary, existing technical solutions all follow a design approach of single-function coating or single-structure optimization for the entire umbrella, failing to distinguish between the two completely different icing mechanisms: the icing zone caused by supercooled water impact on the upper surface of the umbrella and the icicle growth zone along the lower edge of the umbrella. Therefore, they cannot simultaneously achieve coordinated protection by reducing icing at the source and preventing the penetration of icicles in the middle section. Furthermore, traditional semiconductor glazes and hydrophobic glazes have inherent defects in cost control, firing process adaptability, and high-voltage leakage suppression, making it difficult to balance anti-icing performance, operational reliability, and economy. Therefore, the industry urgently needs an anti-icing porcelain insulator solution that can precisely protect different icing areas, is cost-effective, and has a firing process compatible with conventional electric porcelain kilns. Summary of the Invention

[0005] To overcome the shortcomings of existing technologies in terms of anti-icing mechanism adaptability, raw material cost, firing compatibility and production yield, this invention aims to provide a high-voltage line insulator with self-cleaning anti-icing coating that can provide zoned differentiated protection, has controllable cost and is compatible with conventional electric porcelain kilns.

[0006] The objective of this invention is achieved through the following technical solution:

[0007] A self-cleaning, anti-icing high-voltage line insulator includes a porcelain insulator, an iron cap, and steel feet. The porcelain insulator is integrally formed with an umbrella-shaped structure. The surface of the porcelain insulator is divided into three zones: A, B, and C. The three zones share the same base white glaze, and the difference in the coefficient of thermal expansion between the three zones is <0.3×10⁻⁶. -6 / K;

[0008] Region A is a narrow annular band 0-3 cm from the edge of the umbrella, covered with a single layer of weakly semi-conductive glaze. This glaze contains silicon carbide micropowder and flake graphite. After firing, the volume resistivity of Region A is 10⁻⁶. 8 ~10 9 Ω·cm;

[0009] The B area is the entire upper surface of the umbrella, which is covered with fluorine-modified nano-hydrophobic glaze, with a water contact angle ≥145° and a roll-off angle ≤10°.

[0010] The C area refers to the surface of the ceramic insulating component other than the A and B areas, which is covered with a basic white glaze.

[0011] The A and B areas form a gradient overlapping zone of glaze at the umbrella ridge.

[0012] Furthermore, the base white glaze is a feldspar-quartz-kaolin system with a coefficient of thermal expansion of 5.0–5.5 × 10⁻⁶. -6 / K; The weak semiconductor glaze has a single-layer structure, with the basic white glaze as the matrix, and 5-8 wt% silicon carbide micro powder and 1-2 wt% flake graphite added, with a glaze layer thickness of 0.25 mm to 0.35 mm; The fluorine-modified nano hydrophobic glaze has the basic white glaze as the matrix, and 5-7 wt% fumed silica, 2-3 wt% silicon nitride whiskers and 0.2-0.3 wt% perfluorodecyltrimethoxysilane added.

[0013] Furthermore, the diameter of the ceramic insulating disc is 250-760mm, suitable for voltage levels of 10kV-220kV; the lower surface of the umbrella skirt is provided with 3 non-radial offset support ribs, the cross-sectional radius of the support ribs is 8mm-15mm, and the longitudinal distance between the support ribs and the umbrella edge is 40mm-60mm; the width of the glaze layer gradient overlap band is 5mm-8mm.

[0014] Furthermore, the mass ratio of silicon carbide micro powder to flake graphite in the weak semiconductor glaze is (3-5):1, and the equivalent permeation volume fraction of silicon carbide micro powder and flake graphite in the glaze is 12%-14%; the leakage current of area A under a 110kV operating voltage is 30-80μA.

[0015] Furthermore, the ceramic insulating component has the following composition by mass: 20%–22% low-sodium feldspar, 22%–26% α-Al2O3, 18%–22% kaolin, 20%–25% clay, 4%–6% calcite, and 2%–4% talc.

[0016] Furthermore, in the ceramic insulator with a disc diameter of 600mm to 760mm that is compatible with 220kV, the mass fraction of silicon carbide micro powder in area A is 5wt%, and the leakage current of a single piece is ≤50μA.

[0017] The present invention also provides a manufacturing process for the above-mentioned self-cleaning anti-icing high-voltage line insulator, comprising the following steps:

[0018] The green body is bisque fired, and then heated to 1290℃~1310℃ in the kiln and held for 1h~1.5h. The oxygen content in the kiln is controlled at 1vol%~3vol%, and the positive pressure in the furnace is maintained at 40Pa~60Pa.

[0019] For zoned rotary glazing, first invert the insulator, rotate the glazing bucket and use the inner and outer retaining rings to spray only the 0-3cm annular area under the umbrella with weak semiconducting glaze in area A; then install the insulator upright and use a wide-mouth glazing bucket to spray the fluorine-modified nano hydrophobic glaze in area B, so that the glaze slurry naturally extends to form a 5mm-8mm gradient overlap band; finally, use a low-pressure spray gun to avoid area B and spray the basic white glaze in area C.

[0020] Glaze firing: The glazed body is heated to 1080℃~1120℃ and held for 20min~30min. The oxygen content in the kiln is controlled at 1vol%~2vol%, and the positive pressure in the furnace is maintained at 40Pa~60Pa. The cooling stage adopts segmented cooling.

[0021] Furthermore, the specific gravity of the glaze slurry in the weak semiconductor glaze of region A is 1.65 to 1.70, and the glaze spinning speed is 120 rpm to 150 rpm.

[0022] The specific gravity of the fluorine-modified nano-hydrophobic glaze in region B is 1.60 to 1.65, and the glaze spinning speed is 100 rpm to 130 rpm.

[0023] The preparation method of the fluorine-modified nano-hydrophobic glaze in region B is as follows: the basic white glaze, fumed silica and silicon nitride whiskers are ball-milled together for 4h to 6h, and after milling, perfluorodecyltrimethoxysilane is added at low speed for 10min to 20min.

[0024] Furthermore, the segmented cooling in the glaze firing process is as follows: rapid cooling from 1120℃ to 700℃ at a rate of 300℃ / h to 400℃ / h, slow cooling from 700℃ to 300℃ at a rate of 120℃ / h to 180℃ / h, and natural cooling below 300℃; the open porosity of the bisque-fired body is ≤4.5%.

[0025] Furthermore, the basic white glaze has the following composition by mass: 25% potassium feldspar, 20% quartz, 15% kaolin, 8% calcite, 5% talc, 2% ZnO, and 25% clay.

[0026] Compared with the prior art, the beneficial effects of the present invention are:

[0027] ① This invention breaks through the design limitations of traditional single-function coatings for all umbrellas. For the first time, it differentiates and precisely protects the supercooled water impact icing area on the umbrella surface from the icing zone and the melting drip ice ridge growth area along the umbrella's lower edge based on the regional differentiation mechanism of ice flash failure in porcelain insulators in heavy icing zones. The hydrophobic glaze in area B on the umbrella surface, with a high water contact angle of ≥145° and a low roll-off angle of ≤10°, causes supercooled water droplets to roll off the umbrella surface before freezing, inhibiting the formation of initial icing at the source. The weakly semiconductor glaze in area A along the umbrella's lower edge utilizes a semiconductor network composed of silicon carbide and flake graphite to generate controllable Joule heating under a high-voltage electric field, implementing localized directional melting of ice ridges in the ice ridge growth area along the umbrella's lower edge and blocking the through-path of ice ridges in adjacent umbrella skirts. The two areas complement each other and work synergistically to simultaneously achieve the dual protection goals of "ice reduction at the source" and "ice ridge blocking in the middle section," fundamentally solving the inherent contradictions of accelerated ice ridge bridging when using traditional hydrophobic glaze for full umbrella coverage and excessive leakage when using traditional self-heating glaze for full umbrella coverage.

[0028] ② The weakly semiconductor glaze in area A and the hydrophobic glaze in area B share the same feldspar-quartz-kaolin-based white glaze system, and the difference in the coefficient of thermal expansion among the three areas is strictly controlled within 0.3×10. -6 Within a range of / K, and with a 5mm to 8mm gradient overlap zone between areas A and B at the umbrella ridge, the thermal stress abrupt change between dissimilar glaze layers is effectively eliminated, avoiding the process defects of interface cracks easily caused by thermal expansion mismatch in traditional multi-layer composite conductive glazes. Simultaneously, the weak semiconductor glaze in area A adopts a single-layer structure, eliminating the need for the cumbersome process of three-layer composite of traditional silicon carbide conductive glaze base material, conductive layer, and protective layer, and three firings. This significantly simplifies the glazing and firing process, substantially improves mass production efficiency, and reduces manufacturing costs.

[0029] ③The weakly semiconductor glaze in area A uses silicon carbide micropowder and flake graphite as functional fillers. By controlling the mass ratio of the two to be (3-5):1 and the equivalent percolation volume fraction to be 12%-14%, the glaze layer is in a weakly semiconductor state rather than a fully conductive state, and the volume resistivity is stabilized at 10. 8 ~10 9The range is Ω·cm. This setting ensures sufficient Joule heating under high-voltage electric fields for directional de-icing while strictly limiting leakage current levels. Specifically, under 110kV conditions, the leakage current of a single chip is only 30μA to 80μA. For 220kV compatible products, by reducing the silicon carbide doping to 5wt%, the leakage current can be controlled below 50μA, which is far lower than the 300μA leakage level of traditional full-umbrella semiconductor glazes, completely solving the industry problem of excessive power consumption under high-voltage conditions.

[0030] ④ The material system of this invention fully considers both cost controllability and compatibility with firing processes. The weak semiconductor glaze in region A abandons the expensive functional fillers and rare earth dopants in tin-antimony-iron solid solutions and barium titanate-based PTC materials, and uses low-cost silicon carbide and flake graphite as semiconductor functional phases, significantly reducing raw material costs. More importantly, this glaze system has no stringent requirements for the firing atmosphere. Both the bisque firing and glaze firing processes can be adapted to conventional electric porcelain reduction kilns. The oxygen content is controlled at 1-3 vol% during the bisque firing stage and 1-2 vol% during the glaze firing stage, with a furnace positive pressure of 40-60 Pa. It is fully compatible with the existing kiln equipment and process routes of mainstream electric porcelain manufacturers, eliminating the need for dedicated high-oxygen kilns, greatly reducing the equipment investment threshold for industrialization, and possessing good prospects for industrial promotion.

[0031] ⑤ This invention further ensures the stability of product performance through the coordinated design of two-stage firing processes: bisque firing and glaze firing. After bisque firing at 1290℃~1310℃, the open porosity of the body is ≤4.5%, providing a dense base with moderate anchoring force for subsequent glazing. During the glaze firing stage, a segmented cooling strategy of rapid cooling from 1120℃ to 700℃ and slow cooling from 700℃ to 300℃ is adopted, effectively controlling the crystallization and residual stress distribution of the glaze layer, ensuring the bonding strength and long-term service reliability of the glaze layers in the three zones. In addition, the three non-radial offset support ribs set on the lower surface of the umbrella skirt form a spatial synergy with the directional ice melting function of zone A. While mechanically blocking the continuous growth of ice columns, the offset design of the support ribs does not hinder the electric field distribution and Joule heat concentration of the narrow glaze surface in zone A, further enhancing the comprehensive effect of anti-icing flash. Attached Figure Description

[0032] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings:

[0033] Figure 1 This is a cross-sectional view of the self-cleaning anti-icing high-voltage line insulator in the embodiment.

[0034] In the diagram: 1. Porcelain insulator; 2. Iron cap; 3. Steel foot; 4. Area A; 5. Area B; 6. Area C; 7. Non-radial offset support rib. Detailed Implementation

[0035] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0036] All embodiments and comparative examples used the following basic white glaze and body, and were tested under the following uniform ice-covering test conditions.

[0037] The basic white glaze composition is as follows: 25% potassium feldspar, 20% quartz, 15% kaolin, 8% calcite, 5% talc, 2% ZnO, and 25% ball milling. The above components are mixed and ball milled until the residue on a 250-mesh sieve is <0.3%, and the glaze slurry has a reference specific gravity of 1.58.

[0038] The composition of the blank is as follows: 22% low-sodium feldspar, 26% α-Al2O3, 20% kaolin, 24% clay, 5% calcite, and 3% talc; it is formed by isostatic pressing, and the moisture content of the blank is 19.5%.

[0039] The unified testing conditions for icing are as follows: -10℃ in a cold storage environment, continuous supercooled water mist spraying for 2 hours to simulate icing; power frequency voltage is increased until surface flashover, and the ice flashover voltage is recorded, with the test value of conventional XP-160 insulators as 100% of the benchmark.

[0040] Example 1:

[0041] The self-cleaning anti-icing high-voltage line insulator in this embodiment includes a porcelain insulator 1, an iron cap 2, and a steel foot 3. The porcelain insulator 1 is integrally formed with an umbrella skirt structure. The diameter of the porcelain insulator 1 is 520mm, and the voltage level is 110kV. The lower surface of the umbrella skirt is provided with 3 non-radial offset support ribs 7. The surface of the porcelain insulator 1 is glazed in sections, which are divided into sections A 4, B 5, and C 6.

[0042] Area A4 is a narrow annular band 23cm from the edge of the umbrella, covered with a single layer of weak semiconducting glaze. The weak semiconducting glaze uses a base white glaze as its matrix and contains, by mass percentage, 73% base white glaze, 7% silicon carbide micro powder with a particle size of 5μm, 1.5% 300-mesh flake graphite, and 1% nano zinc oxide. The glaze slurry has a specific gravity of 1.67, a wet film thickness of 0.3mm, and a glaze layer thickness of 0.3mm after firing.

[0043] Area B5 is the entire upper surface of the umbrella, which is covered with fluorine-modified nano-hydrophobic glaze. The fluorine-modified nano-hydrophobic glaze uses a base white glaze as the matrix and contains, by mass percentage, 83% base white glaze, 6% 25nm fumed silica, 2.5% silicon nitride whiskers, and 0.25% perfluorodecyltrimethoxysilane. During preparation, the base white glaze, fumed silica, and silicon nitride whiskers are first ball-milled for 5 hours. After milling, silane is added and stirred at low speed for 15 minutes. The specific gravity of the glaze slurry is 1.60.

[0044] Area C6, which includes the sides, disc, and head of the umbrella, is treated with a low-pressure spray gun to apply a base white glaze. Areas A4 and B5 naturally form a 5mm to 8mm gradient overlap of the glaze layer at the umbrella ridges.

[0045] The firing process follows the two-stage firing system of this invention. The kiln atmosphere is neutral with a slight oxidizing effect, and the oxygen volume fraction is about 1.5%. The bisque body is bisque fired at 1300℃ for 1.2 hours with 1.5 vol% oxygen and a positive pressure of 50 Pa in the furnace. After glazing, the glaze is fired at 1100℃ for 30 minutes with 1.5 vol% oxygen and a positive pressure of 50 Pa in the furnace. The cooling adopts a staged system: rapid cooling at 350℃ / h from 1100℃ to 700℃, slow cooling at 150℃ / h from 700℃ to 300℃, and natural cooling below 300℃.

[0046] The volume resistivity of product region A was obtained. The leakage current at 110kV is 38-67μA; the water contact angle in zone B is 148° and the roll-off angle is 8°; the glaze layer in zones three is well bonded and there are no interface cracks; the open porosity of the bisque is 4.2% and the flash voltage is +16.3% relative to the reference.

[0047] Example 2:

[0048] The self-cleaning anti-icing high-voltage line insulator in this embodiment includes a porcelain insulator 1, an iron cap 2, and a steel foot 3. The porcelain insulator 1 is integrally formed with an umbrella skirt structure. The diameter of the porcelain insulator 1 is 480mm, and the voltage level is 110kV. The lower surface of the umbrella skirt is provided with 3 non-radial offset support ribs 7. The surface of the porcelain insulator 1 is glazed in sections, which are divided into sections A 4, B 5, and C 6.

[0049] Area A4 is a narrow annular band 2cm from the edge of the umbrella, covered with a single layer of weak semiconducting glaze. The weak semiconducting glaze uses a base white glaze as its matrix and contains, by mass percentage, 73% base white glaze, 7% silicon carbide micro powder with a particle size of 5μm, 1.5% 300-mesh flake graphite, and 1% nano zinc oxide. The glaze slurry has a specific gravity of 1.67, a wet film thickness of 0.3mm, and a glaze layer thickness of 0.3mm after firing.

[0050] Area B5 is the entire upper surface of the umbrella, which is covered with fluorine-modified nano-hydrophobic glaze. The fluorine-modified nano-hydrophobic glaze uses a base white glaze as the matrix and contains, by mass percentage, 83% base white glaze, 6% 25nm fumed silica, 2.5% silicon nitride whiskers, and 0.25% perfluorodecyltrimethoxysilane. During preparation, the base white glaze, fumed silica, and silicon nitride whiskers are first ball-milled for 5 hours. After milling, silane is added and stirred at low speed for 15 minutes. The specific gravity of the glaze slurry is 1.62.

[0051] Area C6, which includes the sides, disc, and head of the umbrella, is treated with a low-pressure spray gun to apply a base white glaze. Areas A4 and B5 naturally form a 5mm to 8mm gradient overlap of the glaze layer at the umbrella ridges.

[0052] The firing process follows the two-stage firing system of this invention. The kiln atmosphere is neutral with a slight oxidizing effect, and the oxygen volume fraction is about 1.5%. The bisque body is bisque fired at 1300℃ for 1.2 hours with 1.5 vol% oxygen and a positive pressure of 50 Pa in the furnace. After glazing, the glaze is fired at 1100℃ for 30 minutes with 1.5 vol% oxygen and a positive pressure of 50 Pa in the furnace. The cooling adopts a staged system: rapid cooling at 350℃ / h from 1100℃ to 700℃, slow cooling at 150℃ / h from 700℃ to 300℃, and natural cooling below 300℃.

[0053] The volume resistivity of product region A was obtained. The leakage current at 110kV is 32-50μA; the water contact angle in zone B is 148° and the roll-off angle is 8°; the glaze layer in zones three is well bonded and there are no interface cracks; the open porosity of the bisque is 4.3% and the flash voltage is +15.3% relative to the reference.

[0054] Example 3:

[0055] The self-cleaning anti-icing high-voltage line insulator in this embodiment includes a porcelain insulator 1, an iron cap 2, and a steel foot 3. The porcelain insulator 1 is integrally formed with an umbrella skirt structure. The diameter of the porcelain insulator 1 is 740mm, and the voltage level is 220kV. The lower surface of the umbrella skirt is provided with 3 non-radial offset support ribs 7. The surface of the porcelain insulator 1 is glazed in sections, which are divided into sections A 4, B 5, and C 6.

[0056] Area A4 is a narrow annular band 2cm from the edge of the umbrella, covered with a single layer of weak semiconducting glaze. The weak semiconducting glaze uses a base white glaze as its matrix and contains, by mass percentage, 73% base white glaze, 5% silicon carbide micro powder with a particle size of 5μm, 1% 300-mesh flake graphite, and 1% nano zinc oxide. The glaze slurry has a specific gravity of 1.67, a wet film thickness of 0.3mm, and a glaze layer thickness of 0.3mm after firing.

[0057] Area B5 is the entire upper surface of the umbrella, which is covered with fluorine-modified nano-hydrophobic glaze. The fluorine-modified nano-hydrophobic glaze uses a base white glaze as the matrix and contains, by mass percentage, 83% base white glaze, 6% 25nm fumed silica, 2.5% silicon nitride whiskers, and 0.25% perfluorodecyltrimethoxysilane. During preparation, the base white glaze, fumed silica, and silicon nitride whiskers are first ball-milled for 5 hours. After milling, silane is added and stirred at low speed for 15 minutes. The specific gravity of the glaze slurry is 1.62.

[0058] Area C6, which includes the sides, disc, and head of the umbrella, is treated with a low-pressure spray gun to apply a base white glaze. Areas A4 and B5 naturally form a 5mm to 8mm gradient overlap of the glaze layer at the umbrella ridges.

[0059] The firing process follows the two-stage firing system of this invention. The kiln atmosphere is neutral with a slight oxidizing effect, and the oxygen volume fraction is about 1.5%. The bisque body is bisque fired at 1300℃ for 1.2 hours with 1.5 vol% oxygen and a positive pressure of 50 Pa in the furnace. After glazing, the glaze is fired at 1100℃ for 30 minutes with 1.5 vol% oxygen and a positive pressure of 50 Pa in the furnace. The cooling adopts a staged system: rapid cooling at 350℃ / h from 1100℃ to 700℃, slow cooling at 150℃ / h from 700℃ to 300℃, and natural cooling below 300℃.

[0060] The volume resistivity of product region A was obtained. 220kV single-piece leakage current ≤45μA; B zone 5 water contact angle 148°, roll-off angle 8°; good glaze bonding in three zones, no interface cracks; open porosity of bisque 4.3%, ice flash voltage relative to the reference +14.2%.

[0061] Comparative Example 1:

[0062] This comparative example is based on the existing full-umbrella hydrophobic scheme. The insulator disc diameter is 520mm, and the lower surface of the umbrella skirt is provided with 3 non-radial offset support ribs 7. The entire umbrella surface is coated with fluorine-modified nano hydrophobic glaze with the same formula as in Example 1. The weak semiconducting glaze layer in area A4 is not set. The remaining structural parameters are the same as in Example 1.

[0063] Testing showed that the water contact angle of the glaze in this comparative example was 146°, which is comparable to the hydrophobic performance of area B5 in Example 1. However, its ice flash voltage increase was only 3.7% of the baseline value. The underlying mechanism is that the lower edge of the umbrella is the core area for ice growth. The hydrophobic surface properties actually accelerate the formation of melt droplets into beads and their rapid downward extension along the umbrella edge, thus intensifying ice bridging. The positive benefit of the hydrophobic glaze in reducing icing on the umbrella surface is offset by the accelerated ice growth at the lower edge of the umbrella. A single hydrophobic solution cannot meet the anti-icing requirements of heavy icing areas.

[0064] Comparative Example 2:

[0065] This comparative example adopts the partitioned glazing structure of the present invention, namely the three-part partition scheme of A zone 4, B zone 5, and C zone 6 described in Example 1. The material composition and glazing process are completely consistent with Example 1. The only difference is that the kiln atmosphere in the glazing firing process is changed from the neutral oxygen-biased atmosphere of Example 1, i.e., oxygen 1.5 vol%, to the traditional electric porcelain reducing flame atmosphere, with the oxygen volume fraction controlled at 0.3 vol%. The rest of the firing temperature, holding time, and cooling regime are the same as in Example 1.

[0066] Tests showed that the volume resistivity of region A4 in this comparative example decreased to [value missing]. At a 110kV operating voltage, the leakage current reached as high as 1.2mA, severely exceeding the safe operating limit, while the ice flash voltage increase was only 5.4%. The mechanism is analyzed as follows: the reducing atmosphere strips the silicon dioxide passivation layer from the surface of the silicon carbide micropowder, leading to a significant increase in the semiconductor conductive pathway. The glaze layer changes from a weak semiconductor state to a near-conductive state, resulting in uncontrolled leakage current. Simultaneously, the surge in leakage current power consumption triggers a risk of localized overheating. This comparative example demonstrates that the neutral oxygen atmosphere defined in this invention is the key process window for maintaining the 4SiC glaze in region A in a suitable weak semiconductor state.

[0067] Comparative Example 3:

[0068] This comparative example uses the partitioned glazing structure and material composition of the present invention, which is completely consistent with Example 1. The only difference is that the kiln atmosphere in the glazing process is changed to a strong oxidizing atmosphere, and the oxygen volume fraction is controlled at 4 vol%, simulating the strong oxidizing firing system of existing Sn-Sb semiconductor glazes. The other process parameters are the same as those in Example 1.

[0069] Tests showed that the volume resistivity of region A4 in this comparative example increased to [value missing]. Under a 110kV operating voltage, the leakage current was only 8μA, indicating a significant deficiency in self-heating heat, and the ice flash voltage increase was only 6.1%. The underlying mechanism is that the strong oxidizing atmosphere significantly thickened the silica insulating passivation layer on the surface of the silicon carbide micropowder, excessively suppressing the conductive network of the weakly semiconducting glaze. The Joule heating power could not meet the energy requirements for directional ice melting along the umbrella's edge, preventing timely drying of the molten droplets, leading to continuous ice ridge growth and eventual penetration. This comparative example further confirms the necessity of precise control over the glaze firing atmosphere in this invention.

[0070] Comparative Example 4:

[0071] This comparative example is a pure structural improvement scheme. The insulator disc diameter is 520mm, and the lower surface of the umbrella skirt is provided with 3 non-radial offset support ribs 7. The entire umbrella surface is only coated with ordinary basic white glaze, and the weak semiconducting glaze layer in area A 4 and the hydrophobic glaze layer in area B 5 are not set. The remaining structural parameters are the same as those in Example 1.

[0072] Testing showed that the ice flash voltage improvement in this comparative example was 9.2% of the baseline value. However, in Embodiment 1 of this invention, after adding a zoned functional glaze layer to the same structure, the ice flash voltage improvement reached 16.3%. Comparing the two, it is clear that pure structural optimization has a limited effect on improving the ice flash voltage and is insufficient to meet the operational requirements of heavy icing areas. The structural improvement and the zoned functional glaze layer of this invention have a significant synergistic effect; the combined anti-icing effect is superior to the simple superposition of their individual effects, demonstrating the superiority of the zoned protection technology approach of this invention.

[0073] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A self-cleaning, anti-icing high-voltage line insulator, comprising a porcelain insulator (1), an iron cap (2), and a steel foot (3), wherein the porcelain insulator (1) is integrally formed with an umbrella skirt structure, characterized in that, The surface of the ceramic insulating component (1) is glazed in sections, namely, section A (4), section B (5) and section C (6). The three sections share the same basic white glaze and the difference in the coefficient of thermal expansion of the three sections is <0.3×10-6 / K. The A region (4) is a narrow annular band 0-3 cm from the edge of the umbrella, covered with a single layer of weak semiconducting glaze. The weak semiconducting glaze contains silicon carbide micro powder and flake graphite. After firing, the volume resistivity of the A region (4) is 108-109 Ω·cm. The B area (5) is the entire upper surface of the umbrella, which is covered with fluorine-modified nano hydrophobic glaze, with a water contact angle ≥145° and a roll-off angle ≤10°. The C area (6) is the surface of the ceramic insulating part (1) other than the A area (4) and the B area (5), which is covered with a basic white glaze; The A region (4) and the B region (5) form a gradient overlapping zone of glaze at the umbrella ridge.

2. The self-cleaning, anti-icing high-voltage line insulator according to claim 1, characterized in that, The basic white glaze is a feldspar-quartz-kaolin system with a thermal expansion coefficient of 5.0–5.5 × 10⁻⁶ / K. The weakly semiconductor glaze is a single-layer structure, with the basic white glaze as the matrix and 5–8 wt% silicon carbide micro powder and 1–2 wt% flake graphite added, with a glaze layer thickness of 0.25 mm–0.35 mm. The fluorine-modified nano-hydrophobic glaze is with the basic white glaze as the matrix and 5–7 wt% fumed silica, 2–3 wt% silicon nitride whiskers, and 0.2–0.3 wt% perfluorodecyltrimethoxysilane added.

3. The self-cleaning anti-icing high-voltage line insulator according to claim 1, characterized in that, The ceramic insulator (1) has a disc diameter of 250-760mm and is suitable for voltage levels of 10kV-220kV; the lower surface of the umbrella skirt is provided with 3 non-radial offset support ribs (7), the cross-sectional radius of the support rib is 8mm-15mm, and the longitudinal distance between the support rib and the umbrella edge is 40mm-60mm; the width of the glaze layer gradient overlap band is 5mm-8mm.

4. The self-cleaning anti-icing high-voltage line insulator according to claim 2, characterized in that, The mass ratio of silicon carbide micro powder to flake graphite in the weak semiconductor glaze is (3-5):1, and the equivalent permeation volume fraction of silicon carbide micro powder and flake graphite in the glaze is 12%-14%; the leakage current of area A (4) under a 110kV operating voltage is 30-80μA.

5. The self-cleaning anti-icing high-voltage line insulator according to any one of claims 1-4, characterized in that, The ceramic insulating component (1) has the following composition by mass: 20%–22% low-sodium feldspar, 22%–26% α-Al2O3, 18%–22% kaolin, 20%–25% spherical clay, 4%–6% calcite, and 2%–4% talc.

6. The self-cleaning anti-icing high-voltage line insulator according to claim 4, characterized in that, In the ceramic insulator (1) with a disc diameter of 600mm to 760mm that is compatible with 220kV, the mass fraction of silicon carbide micro powder in area A (4) is 5wt%, and the single-piece leakage current is ≤50μA.

7. A manufacturing process for a self-cleaning, anti-icing high-voltage line insulator as described in any one of claims 1 to 6, characterized in that, Includes the following steps: The green body is bisque fired, and then heated to 1290℃~1310℃ in the kiln and held for 1h~1.5h. The oxygen content in the kiln is controlled at 1vol%~3vol%, and the positive pressure in the furnace is maintained at 40Pa~60Pa. For the zonal rotation glazing, first turn the insulator upside down, rotate the glazing bucket and use the inner and outer retaining rings to spray only the 0-3cm annular area under the umbrella with the weak semiconducting glaze of area A (4); then turn the insulator upright and use the wide-mouth glazing bucket to spray the fluorine-modified nano hydrophobic glaze of area B (5), so that the glaze paste naturally extends to form a 5mm-8mm gradient overlapping band; finally, use a low-pressure spray gun to avoid area B (5) and spray the basic white glaze of area C (6); Glaze firing: The glazed body is heated to 1080℃~1120℃ and held for 20min~30min. The oxygen content in the kiln is controlled at 1vol%~2vol%, and the positive pressure in the furnace is maintained at 40Pa~60Pa. The cooling stage adopts segmented cooling.

8. The preparation process according to claim 7, characterized in that, The specific gravity of the glaze slurry in the weak semiconductor glaze of region A (4) is 1.65 to 1.70, and the glaze spinning speed is 120 rpm to 150 rpm. The specific gravity of the fluorine-modified nano-hydrophobic glaze in region B (5) is 1.60 to 1.65, and the glaze spinning speed is 100 rpm to 130 rpm. The preparation method of the fluorine-modified nano-hydrophobic glaze in region B (5) is as follows: the basic white glaze, fumed silica and silicon nitride whiskers are ball-milled together for 4h to 6h, and after milling, perfluorodecyltrimethoxysilane is added at low speed for 10min to 20min.

9. The preparation process according to claim 7, characterized in that, The segmented cooling process in the glaze firing process is as follows: rapid cooling from 1120℃ to 700℃ at a rate of 300℃ / h to 400℃ / h, slow cooling from 700℃ to 300℃ at a rate of 120℃ / h to 180℃ / h, and natural cooling below 300℃. The open porosity of the bisque-fired green body is ≤4.5%.

10. The preparation process according to claim 7, characterized in that, The basic white glaze has the following composition by mass: 25% potassium feldspar, 20% quartz, 15% kaolin, 8% calcite, 5% talc, 2% ZnO, and 25% clay.